Medical Rehabilitation and National Health Insurance Era in Indonesia - Anshory Sahlan (Indonesian Journal of Physical Medicine & Rehabilitation, 2019)
Rehabilitation has become one of the keys to health strategy for the 21st Century. Demographic and epidemiological shifting trends to the rise in life expectancy and the growing number of chronic noncommunicablediseases are creating rehabilitation needs. However, the capacity to provide rehabilitation is still limited or non-existent and fails to adequately address the needs of the population. In 2017 WHOhas made a strategy to scale up rehabilitation for greater awareness and advocacy, also increase investment into rehabilitation workforce and infrastructure known as Rehabilitation 2030: A Call for Action. Thereforecountries are called to coordinate and concert global action towards strengthening rehabilitation in health systems, including in Indonesia.